PEMBUATAN BIOETANOL DARI LIMBAH SERAT KELAPA SAWIT MELALUI PROSES PRETREATMENT, HIDROLISIS ASAM DAN FERMENTASI MENGGUNAKAN RAGI TAPE - Lailan Ni'mah; Angga Ardiyanto; Muhammad Zainuddin (Universitas Lambung Mangkurat, 2015)
Palm fiber cake is a waste of the palm oil industry or crude palm oil (CPO). Oil palm fiber waste can be used as raw material for second-generation bioethanol because it contains 57.9% cellulose dan18% lignin, and the hydrolysis containing 14.94% hemicellulose. This study was used the process of pretreatment, hydrolysis, neutralization, and fermentation with the purpose to obtain bioethanol. Oil palm fiber was cut to the size of 0.5-1 cm. Then pretreated using acid solvent by heating at 100 ° C for 1 hour with a hot plate stirrer. Solids pretreatment results are mixed with distilled water to concentrations (5% w/v) is prepared to hydrolysis. The solids are then dissolved with a solution of H2SO4 (2% v/v) to 500 ml and dihidrolisisis for 120 minutes with a temperature variation of 115 °C, 120 °C, 125 °C objective to determine the influence of optimal temperature in the process of hydrolysis using an autoclave. Hydrolyzate is neutralized with 1 N NaOH until pH 5 and the sugar content by the Luff-Schoorl method obtained the highest sugar content of 9.69% v/v. Hydrolyzate that has been in the neutralization fermented with yeast and nutrients NPK tape with glass bottles that have been sterilized using an autoclave fermented for 3 days. Fermented ethanol levels were tested by analysis by Gas Chromatography (GC) is known to the highest bioethanol content of 2.858% (v/v). Peak Characteristic of oil palm fiber cellulose before and after pretreatment of cellulose fiber cake increased by 42.30% (cellulose I) to 48.60% (cellulose II) by X-Ray Difraction. Keywords: Palm fiber cake, acid pretreatment, acid hydrolisis, fermentation, bioethanol.